36.8k views
4 votes
Can someone tell me if I got the answer right? For the first one I got 2 and for the second one I got -1.

Can someone tell me if I got the answer right? For the first one I got 2 and for the-example-1

2 Answers

2 votes

Answer:

see explanation

Explanation:

f(g(2)) = f(0) = -2

g(f(1)) = g(0) = 0

User Nappstir
by
5.6k points
1 vote

Answer:

The correct answers for both of them is -2 and 0.

Explanation:

I)


(f\circ g)(2)=f(g(2))

From the red graph, we can see that g(2) is 0.

Therefore, f(g(2)) is equal to f(0).

And from the blue graph, we can see that f(0) is -2.

Therefore:


(f\circ g)(2)=-2

II)


(g\circ f)(1)=g(f(1))

From the blue graph, we can see that f(1) is 0.

Therefore, g(f(1)) is equal to g(0).

And from the red graph, g(0) is 0.

Therefore:


(g\circ f)(1)=0

So, you got one correct. Nicely done!

User Sigmatics
by
5.9k points